N-Terminus-Mediated Degradation of ACS7 Is Negatively Regulated by Senescence Signaling to Allow Optimal Ethylene Production during Leaf Development in Arabidopsis - Sun, Gongling; Mei, Yuanyuan; Deng, Dewen; Xiong, Li; Sun, Lifang; Zhang, Xiyu; Wen, Zewen; Liu, Sheng; You, Xiang; Nasrullah,; Wang, Dan; Wang, Ning Ning (Frontiers in Plant Science, 2017)
Senescence is the final phase of leaf development, characterized by key processes by which resources trapped in deteriorating leaves are degraded and recycled to sustain the growth of newly formed organs. As the gaseous hormone ethylene exerts a profound effect on the progression of leaf senescence, both the optimal timing and amount of its biosynthesis are essential for controlled leaf development. The rate-limiting enzyme that controls ethylene synthesis in higher plants is ACC synthase (ACS). In this study, we evaluated the production of ethylene and revealed an up-regulation of ACS7 during leaf senescence in Arabidopsis. We further showed that the promoter activity of ACS7 was maintained at a relatively high level throughout the whole rosette development process. However, the accumulation level of ACS7 protein was extremely low in the light-grown young seedlings, and it was gradually restored as plants aging. We previously demonstrated that degradation of ACS7 is regulated by its first 14 N-terminal residues, here we compared the phenotypes of transgenic Arabidopsis overexpressing a truncated ACS7 lacking the 14 residues with transgenic plants overexpressing the full-length protein. Results showed that seedlings overexpressing the truncated ACS7 exhibited a senescence phenotype much earlier than their counterparts overexpressing the full-length gene. Fusion of the 14 residues to SSPP, a PP2C-type senescence-suppressed protein phosphatase, effectively rescued the SSPP-induced suppression of rosette growth and development but had no effect on the delayed senescence. This observation further supported that N-terminus-mediated degradation of ACS7 is negatively regulated by leaf senescence signaling. All results of this study therefore suggest that ACS7 is one of the major contributors to the synthesis of ‘senescence ethylene’. And more importantly, the N-terminal 14 residue-mediated degradation of this protein is highly regulated by senescence signaling to enable plants to produce the appropriate levels of ethylene required.